Web-Based Information System for Monitoring the History of Radio Frequency Spectrum User Violations - Fajriahani, Hajjar; Tri Ana Styarini (Lembaga Pengembangan Kinerja Dosen, 2025)
The radio frequency spectrum is a limited natural resource that is crucial in supporting various communication sectors. However, violations of frequency spectrum usage, such as unauthorized usage or non-compliance with technical parameters, frequently occur in the East Nusa Tenggara region. Monitoring conducted by the Radio Frequency Spectrum Monitoring Center Class I Kupang faces challenges due to manual record-keeping and scattered data, which hinder efficient evaluation and management of violations. This study aims to develop a web-based information system capable of monitoring and recording the history of radio frequency spectrum violations in a centralized and real-time manner. The system is also designed to facilitate easier access to information and management of violation data. Data collection methods used in this research include literature studies, observation, and interviews. Meanwhile, the software development method applied is the Waterfall model, which includes the stages of analysis, design, coding, testing, and maintenance. The result of this research is an information system that provides centralized violation history data to support more effective radio frequency spectrum management in the East Nusa Tenggara region